Rationale and Design of the ACS-BP Study: Prognostic Value of In-Hospital Blood Pressure and Indices of Atherosclerosis in Acute Coronary Syndromes - Koumelli, Areti; Konstantinou, Konstantinos; Kasiakogias, Alexandros; Dimitriadis, Kyriakos; Leontsinis, Ioannis; Mantzouranis, Emmanouil; Tolis, Elias; Fragkoulis, Christos; Ntalakouras, Ioannis; Thomopoulos, Costas; Tousoulis, Dimitrios; Tsioufis, Costas (Current Vascular Pharmacology, 2021)
Background: High blood pressure (BP) is a leading risk factor for coronary artery disease and other major cardiovascular events. Objective: Blood pressure variability (BPV), ambulatory arterial stiffness index (AASI) and ankle- brachial index (ABI) have been proposed as indices that can improve risk stratification for an adverse cardiac outcome. However, their utility in the setting of acute coronary syndromes (ACS) is unclear. Methods: The ACS-BP study is a single-centre observational cohort study designed to investigate the prognostic role of haemodynamic load and arterial stiffness indices for cardio-renal outcomes in patients with acute myocardial infarction (AMI). All consecutive patients admitted with a diagnosis of acute AMI with or without ST segment elevation were screened for inclusion in the study. The management of AMI will follow current guidelines. Results and Discussion: Data from baseline clinical and laboratory parameters during their hospitalization were collected. The haemodynamic load of each patient was determined by clinical BP values as well as 24-h ambulatory BP monitoring. The AASI was calculated from the raw 24-h BP data and ABI was measured after the third day of hospitalization using a certified device. Patients were followed-up for 12 months in order to collect data for hard cardiovascular and renal endpoints. Conclusion: The study results should clarify the role of these non-invasive tools in secondary risk stratification of such patients.
Keywords: arterial stiffness